The Subdistrict Head Duties and the Delegation of Some of the Regent’s Authority Implementation at Sangasanga Subdistrict, Kutai Kartanegara Regency - Sugiansyah, Muliady; Apriani, Fajar; Susilo Utomo , Heryono (CV. Publikasi Indonesia, 2025)
The delegation of the Regent’s authority to Subdistrict Heads under Law No. 23/2014 and Regent’s Decree No. 247/2021 aims to enhance local governance and public service efficiency in Kutai Kartanegara Regency. However, implementation challenges persist. This study examines the execution of delegated authority in Sangasanga Subdistrict, identifying supporting and inhibiting factors. A qualitative case study was conducted using Edwards III’s policy implementation model (communication, resources, disposition, bureaucratic structure). Data were collected via interviews, observation, and documentation from Subdistrict officials and village heads, analyzed through interactive qualitative analysis. While communication and coordination were effective, key obstacles included inadequate human resources (e.g., untrained staff), delayed infrastructure (e.g., ID card printers), limited budgets, and complex administrative procedures. Supporting factors included strong inter-governmental collaboration and administrative streamlining. The study underscores the need for targeted capacity-building, budget reallocation, and simplified procedures to optimize decentralization. It contributes to the discourse on local governance by highlighting the gap between policy design and grassroots implementation.